Analisis Risiko Produksi Cabai Merah Di Kampung Binjai Agung Kecamatan Bekri Kabupaten Lampung Tengah - Sutarni , Sutarni (Politeknik Negeri Lampung, 2023)
One of the risks faced in red chili farming is a decrease in production. To minimize this loss, a risk management strategy for red chili farming production is needed. This study aims to measure and calculate the risk level of red chili farming production, and analyze the causes of red chili farming production risk in Kampung Binjau Agung, Bekri District. Measurement of red chili farming risk was analyzed using opportunity measurement, expected return, analysis of variance, standard deviation, and coefficient of variation and identification of types and sources of risk were analyzed descriptively qualitatively. The results showed that the coefficient of variation (CV) was 0.5716 in 2018 and the coefficient of variation (CV) in 2019 was 0.931. The coefficient of variation (CV) is more than 0.5, which is close to 1, meaning that the risk of red chili production faced by farmers in Kampung Binjai Agung, Bekri District, is very high. Factors that cause a high risk of red chili production are pests and diseases, use of fertilizers and soil fertility, use of seeds, and climate and weather. Pests that often attack red chili plants in Binjai Agung Village are triphs and caterpillars, while diseases that often attack red chili plants in Binjai Agung Village are fusarium wilt and anthracnose (kerepek). To minimize the risk of red chili production, it is necessary to carry out integrated pest and disease control, optimal use of organic, biological and inorganic fertilizers, so that red chili production can increase.